Mediating effect of work motivation on the relationship between competency and professional performance of EFL teachers - Ahmed Boset, Sameer; Adelina Asmawi, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Considerable evidence indicates that teachers’ competency, work motivation, and professional performance are related. However, insufficient research has investigated the mediating effect of work motivation on the relationship between competency and professional performance in the context of teachers of English as a Foreign Language (EFL). Therefore, the main purpose of this paper is to investigate the mediating effect of EFL Teachers’ Work Motivation (EFLTWM) on the relationship between EFL Teachers’ Competency (EFLTC) and EFL Teachers’ Professional Performance (EFLTPP) at public secondary schools in Yemen. The discussion arises primarily based on the considerable theoretical vagueness and empirical inconclusiveness in the existing literature concerning EFL teachers’ competency and work motivation, and their contribution. As of interest to resolve this controversy, a research framework is developed in which EFLTWM acts as the mediator between EFLTC and EFLTPP. For this purpose, three instruments were used to collect data which are: EFL Teachers’ Competency Questionnaire, Multidimensional Work Motivation Scale, and EFL Teachers’ Professional Performance Evaluation Instrument. The sample of this study consisted of 375 female and male EFL teachers at public secondary schools in Yemen who were selected through a simple random sampling technique to be the participants of the study. The partial least squares structural equation modelling (PLS-SEM), using SmartPLS, was performed to test the hypothesized model. Findings revealed that EFLTWM partially mediates the effect of EFLTC on EFLTPP. Based on the findings, some recommendations have been provided and some implications for teacher training have been discussed.